Probing the Interstellar Medium Toward Timing Array Millisecond Pulsars with the Murchison Widefield Array - Kaur, Dilpreet (Curtin University, 2021)
Millisecond pulsars are highly sought-after targets for timing-array experiments that aim to detect ultra-low frequency gravitational waves. However, there are multiple challenges before this goal can be achieved. Interstellar medium effects on pulsar signals are amongst them. The magnitudes of these effects are much stronger at longer radio wavelengths, therefore low-frequency observations with the Murchison Widefield Array are especially promising for the related studies. This thesis presents such a study for two millisecond pulsars.